Coping Strategies to Improve Students’ Emotional Intelligence Through Content Mastery Services - Seila Arfianie; Lusiana Wulandari (Journal of Counseling and Educational Research, 2026)
Increasing emotional dysregulation among adolescents has become a growing concern, particularly due to academic pressure and digital exposure. Emotional intelligence plays a key role in regulating emotions and managing social challenges. This study examines the effectiveness of coping strategies in enhancing students’ emotional intelligence through content mastery services. A quasi-experimental design was conducted with 63 students at SMPN 242 Jakarta, divided into experimental and control groups. Data were analyzed using paired sample t-tests. Results showed a significant improvement in emotional intelligence in the experimental group (p < 0.001) with a moderate to strong effect size, while the control group showed no significant change (p = 0.663). These findings indicate that coping-based interventions effectively support emotional regulation and resilience. This study provides one of the first quasi-experimental evaluations in Indonesian junior high schools and highlights the importance of structured, preventive counseling programs.